2018
DOI: 10.1186/s13053-017-0085-6
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 mutation spectrum – an update on mutation distribution in a large cancer genetics clinic in Norway

Abstract: BackgroundFounder mutations in the two breast cancer genes, BRCA1 and BRCA2, have been described in many populations, among these are Ashkenazi-Jewish, Polish, Norwegian and Icelandic. Founder mutation testing in patients with relevant ancestry has been a cost-efficient approach in such populations. Four Norwegian BRCA1 founder mutations were defined by haplotyping in 2001, and accounted for 68% of BRCA1 mutation carriers at the time. After 15 more years of genetic testing, updated knowledge on the mutation sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
0
23
2
Order By: Relevance
“…Other variants that also lead to skipping of exon 23 have been published as pathogenic, e.g. c.5407-2A>G [11,26], c.5407-10G>A [27], c.5467+1G>A [28] and c.5434C>G (p.Pro1812Ala) [11,29]. Although a wide range of alternative transcripts have been described for the BRCA1 locus [12], there were no signs of aberrant splicing of exon 23 among the 30 normal controls in our study.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Other variants that also lead to skipping of exon 23 have been published as pathogenic, e.g. c.5407-2A>G [11,26], c.5407-10G>A [27], c.5467+1G>A [28] and c.5434C>G (p.Pro1812Ala) [11,29]. Although a wide range of alternative transcripts have been described for the BRCA1 locus [12], there were no signs of aberrant splicing of exon 23 among the 30 normal controls in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…Nevertheless, the BRCA1 variant c.5434C>G is considered a high-risk pathogenic/likely pathogenic variant by several independent groups [11,18,29]. However, most partial splice variants remain VUS [19], leaving patients and doctors in a challenging position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was detected in a patient suffering from ovarian cancer. To the best of our knowledge, this is the first Moroccan study to report this variant however, it was reported in different populations worldwide [61,62].…”
Section: Discussionmentioning
confidence: 77%
“…Participants were excluded if they had a personal history of any type of cancer besides nonmelanoma skin cancer, had ever received genetic counseling or BRCA1/2 testing themselves, had a prophylactic mastectomy or oophorectomy, lived outside the United States, and/or were incarcerated. Women of Ashkenazi Jewish descent were not included because of their elevated risk due to the prevalence of founder mutations in BRCA1/2 (Heramb et al, ).…”
Section: Methodsmentioning
confidence: 99%